Heterobimetallic block copolymers with a combined main-chain/side-chain topology. Issue 2 (8th December 2022) - Sha, Ye; Zhou, Zhou; Zhang, Jiale; Chen, Xiaofan; Luo, Zhenyang; Li, Xiang
Abstract : We report for the first time the synthesis of heterobimetallic block copolymers with a combined main-chain/side-chain topology. Abstract : We report for the first time the synthesis of heterobimetallic block copolymers with a combined main-chain/side-chain topology. The photophysical, electrochemical, and thermal properties and ring-opening metathesis polymerization-induced crystallization-driven self-assembly (ROMPI-CDSA) behavior of these polymers can be significantly modulated by switching the metal identity.